A Methods study on Florante Garments Manufacturing - Antonio, Ashley S. (College of Engineering, University of the Philippines Diliman, March 26, 1992)
Florante Garments Manufacturing is a company which produces and distributes shirts, blouses, sweat pants and sweat shirts. The company started its operation in August of 1983 with only two sewing machines and has grown to more than 40 sewing machines to date. The company is solely owned by Mr. Florante de Castro. The objective of undertaking this methods study in the company is to put into practical use the knowledge of Methods Study and the Systems and Procedures approach in improving the production of shirts. The project team documented the production system of the company under study. Production process starts with inspecting and cutting of fabrics. The cut materials are sorted out and bundled before being transferred to the sewing area which is in another building about 0.6 km. away. All the sewing processes are done in this area and their system is similar to production line where one sewer works on a particular part. Then the sewn shirts are transported back to the finishing area. The shirts undergo trimming, quality control, washing if necessary, pressing, before packing. The group was able to see problem areas in men, methods, management, and machines in the company. There is the absence of a Personnel Manager who could handle all the problems affecting the workers. There is the improper scheduling of materials to be worked upon. As a result the cutting, sewing and finishing areas are congested by the so many piles of stocks. There is also a shortage of workers in sections like sorting and washing. An effect of this is the accumulation of work in the said areas. Lastly, there is the improper layouting. There are wide gaps between sections and crossing of paths occurs. The recommendations of the group tried to solve out these problem areas. A new layout for the finishing area was provided. Proper utilization and scheduling of materials could help decongest the working area. The addition of workers in areas where accumulation of work is visible. The hiring of a personnel manager is also recommended to help in solving problems affecting the workers. With these recommendations, it is expected that there will be increased productivity in the company.